Morpho-molecular Characterization and Phylogenetic Relationship of Tapinoma indicum Forel from Metropolitan Area - Lim, Li Yang; Ab Majid, Abdul Hafiz (Malaysian Applied Biology, 2022)
Tapinoma indicum Forel is one of the most abundant nuisance pests found in Penang Island, Malaysia. However, limited research has been done on T. indicum, especially in the molecular genetic field. This paper aims to collect T. indicum from three districts in Penang Island, Malaysia including George Town, Gelugor, Balik Pulau, characterize T. indicum based on morphological measurements and molecular characterization of T. indicum using mitochondrial cytochrome c oxidase subunits 1 (CO1) sequences and 16S ribosomal DNA (16S rDNA) sequences. The morphological measurements resulting in HL = 4.31 ± 0.12 mm, HW = 3.87 ± 0.06 mm, EL = 0.89 ± 0.05 mm, EW = 0.58 ± 0.01 mm, SL = 3.56 ± 0.08 mm, ML= 1.11 ± 0.12 mm, CI = 89.83 ± 1.17, EI = 20.59 ± 0.88 and SI = 82.95 ± 2.34. The CO1 sequences and 16S rDNA sequences of T. indicum from each population are deposited and accessible via Genbank (NCBI) database. The phylogenetic trees result in two clades with three haplotypes, but the genetic structure is not well revealed.